(3GdHGbjGJ GdUGdMGJs - (3YHO GdHGbj GdaGQhbj , YHO GdHGbj Hf SdjeGf Hf CMeO GdYeQj GdehUdj,J (B1279 (3g` s
(3ChdgG (B:s
(3gPG GdcJGH GdefJbi hGdeLJHi ef fYJ Cgd GdHjJ CUMGH GdYHG HGdbde GdCYdi Hjefi bOQg ai dhM YRI HfhQ cJHG s
(3BNQgG (B:s
(3aPfhHi XgQJ hGNLdJi hcQhHi YUeJ hGNjHJi aCfdfi GdYah hGcTa cQHJi aGSJLH di jG Edgi OYhJi CfJ QHi hQMje GdQMeG s
(3GdcJGH OjhGf TYQi ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B271s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B104 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdMceI , HZOGO (B(94) s
Keywords: (3GdCOHs